UPLC-HRESI-MS and GC-MS analysis of the leaves of Nicotiana glauca - Massadeh Rafeef K.; El-Elimat Tamam; Al-Gharaibeh Mohammad; Tawaha Khaled; Alali Feras Q. (Acta Pharmaceutica)
The alkaloid-rich fraction obtained by fractionation of the crude methanolic extract of the leaves of wild tobacco tree Nicotiana glauca Graham (Solanaceae) was analyzed using UPLC-MS and GC-MS. Anabasine, a piperidine alkaloid, was identified as the major constituent with approximately 60 % (m/m) of the alkaloid-rich fraction. In addition to anabasine, six secondary metabolites were identified using high-resolution UPLC-MS. Anabasine was quantified in the leaves to be 1 mg g−1 dry plant material. The GC-MS analysis revealed five compounds with anabasine as the major component, while nicotine was not detected. Moreover, GC-MS was used for the analysis of the volatile oil that was obtained by hydro-distillation from the leaves of N. glauca. The volatile plant oil was found to be rich in oxygenated sesquiterpenes (e.g., β-bisabolol) and carboxylic acids and esters (e.g., ethyl linoleate and hexadecanoic acid), whereas anabasine was not detected.